Co‐Design of a Facilitated Self‐Management Toolkit for People With Parkinson's Disease - Nathan Davies; Megan Armstrong; Jennifer S. Pigott; Danielle Nimmons; Joy Read; Benjamin Gardner; Bev Maydon; Anette Schrag; Kate Walters (Health Expectations)
ABSTRACT Background Parkinson's disease is a complex progressive neurodegenerative disease increasing globally. Self‐management interventions have shown promise in improving the quality of life for people with chronic conditions. This paper aims to describe the development processes and the core components of a facilitated self‐management toolkit to support people with Parkinson's disease to self‐manage their condition. Methods An iterative co‐design approach was adopted and included the use of systematic reviews, qualitative methods and theory to develop the Live Well with Parkinson's toolkit. A co‐design group was established consisting of people with Parkinson's, family carers and health and social care experts to produce and refine an online self‐management toolkit to be tested in practice. Five co‐design groups were conducted alongside several phases of toolkit development. Results An online self‐management toolkit, called Live Well with Parkinson's, was developed with core aspects such as tailored information to the individual, a well‐being section using an asset‐based approach and problem‐solving skills to create and maintain goals, symptom review and management sections and a tracker of medication, symptoms and activities/actions. A paper‐based alternative version was also created for those who cannot use an online resource. The toolkit is fully manualised and facilitated by six sessions from a ‘supporter’ who is trained in behaviour change techniques. It can be shared with carers and healthcare professionals. Conclusion The toolkit is a robust and comprehensive approach to self‐management of Parkinson's disease. It is evidenced based, incorporates theory and was developed with people with Parkinson's and experts in the area. The Live Well with Parkinson's toolkit has the potential to be embedded within routine healthcare, aligning with self‐management policies. Patient or Public Contribution Author B.M. is our patient and public involvement (PPI) representative and author on this paper. B.M. supports a team of 15 PPI members who have contributed to the development of the toolkit. This involvement has included attending research team and steering group meetings, attending and facilitating co‐designed workshops, reviewing all the toolkit information before approval and supporting with the user testing.